Empowering tomorrow: How youth shape public participation today? - Suhaimi, Safiah; Mohd Nor, Haslina (International Journal of Accounting, Finance and Business, 2025)
Youth engagement in public participation plays a crucial role in building inclusive, dynamic, and democratic societies. This paper reviews recent literature highlighting the benefits of youth involvement in civic activities, organizational and sports participation, and urban planning, emphasizing positive impacts on psychological well-being, social capital, and community development. Despite significant barriers such as socioeconomic challenges, infrastructural limitations, and social exclusion, emerging opportunities through digital platforms and youth-friendly policies have expanded access and inclusivity. The paper underscores the importance of creating supportive frameworks that address structural inequalities, foster mentorship, and actively involve youth in decision-making processes. Future recommendations focus on equitable resource allocation, capacity-building programs, and inclusive policy design to empower youth as active citizens, thereby strengthening democratic governance and sustainable community development.